2011
DOI: 10.1083/jcb.201103105
|View full text |Cite
|
Sign up to set email alerts
|

Release of serine/threonine-phosphorylated adaptors from signaling microclusters down-regulates T cell activation

Abstract: Serine/threonine phosphorylation of the T cell adaptor proteins SLP76 and GADS by HPK1 induces their release from signaling microclusters and subsequent termination of the T cell response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…Further investigation will be required to test this model. In addition to its expression level, Gads availability for signaling may be regulated by post-translational modifications, such as caspasemediated cleavage [49,50] or its phosphorylation at T262 [39]. Both mechanisms have been suggested to promote the release of SLP-76 from the LAT nucleated complex.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Further investigation will be required to test this model. In addition to its expression level, Gads availability for signaling may be regulated by post-translational modifications, such as caspasemediated cleavage [49,50] or its phosphorylation at T262 [39]. Both mechanisms have been suggested to promote the release of SLP-76 from the LAT nucleated complex.…”
Section: Discussionmentioning
confidence: 97%
“…Functional assessment of this site was previously performed by overexpression of murine Gads T254A, in the presence of endogenous wild-type Gads [39]. The Gadsdeficient cell lines described here provided an opportunity to study this site in a cleaner genetic background.…”
Section: Modulation Of Gads Activity By Its Tonic Phosphorylation At mentioning
confidence: 99%
See 1 more Smart Citation
“…Insoluble material was removed by centrifugation at 20,800xg for 10 min at 4°C. Samples were either stored at –20°C or directly fractionated by electrophoresis on Novex NuPage gels (Life Technologies) using MOPS buffer, then transferred to nitrocellulose membranes and analyzed by immunoblotting, as described [13, 16]. …”
Section: Methodsmentioning
confidence: 99%
“…We previously identified a negative feedback loop downregulating TCR signaling and T cell activation, that involves Ser/Thr phosphorylation of SLP76 and GADS by the Hematopoietic Progenitor Kinase (HPK)1 [13, 16], a member of the Germinal Center Kinase family. We have shown that when HPK1 is recruited in early signaling complexes, through its binding to the SLP76 SH2 domain [17], it induces the phosphorylation of Ser376 in SLP76 and Thr262 in GADS.…”
Section: Introductionmentioning
confidence: 99%